Peroneal nerve involvement as initial manifestation of primary systemic vasculitis - Ripellino, Paolo; Varrasi, Claudia; Maldi, Elena; Cantello, Roberto (BMJ case reports, 2014)
We report a case of two patients with foot drop due to peroneal nerve infarct as early sign of two different forms of primary systemic vasculitides: a predominantly small-vessel p-antineutrophil cytoplasmic antibody-positive vasculitis (microscopic polyangiitis) and a predominantly medium-vessel vasculitis (polyarteritis nodosa).